PENGARUH SUHU DAN KONSENTRASI ENZIM AMILOGLUKOSIDASEPADA PROSES SAKARIFIKASI TERHADAP PRODUKSI GULA CAIR PATI UBI TALAS (Colocasia esculenta) - Wijaya Putra, I Kadek Adi; Hartiati, Amna; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The experiment was carried out todetermine the effect of amyloglucosidase concentration and temperature of saccharification process on the characteristics ofliquid sugar and to find out the best characteristics of liquid sugar from taro potato starch. This study used a split plot experimental design with two treatment factors. The main plot was the saccharification temperature which consists of three levels, namely 55°C, 60°C and 65°C. Amyloglucosidase enzyme concentration as the subplot consisted of three levels ie 1500 U/kg of starch, 2500 U/kg of starch and 3500 U/kg of starch. In this experiment obtained 9 combinations for each experiment was repeated 2 times and obtained 18 experimental units. The results of liquid sugar were then analyzedtheir moisture content, ash content, degree of sweetness, and sensory test color. The results showed that the addition of enzyme amyloglucosidase with different concentrations significantly affected the degree of sweetness and gave a very significant effect on the color of liquid sugar and no significant effect on moisture content and ash content. The difference treatment of Saccharification temperature significantly affected the water content, the degree of sweetness and color and no gave significant effect on ash content of liquid sugar. Interaction between treatments significantly affected the degree of sweetness, very significant effect on the color and no significant effect on moisture content and ash content of the resulting liquid sugar. The treatment with the addition of enzyme amyloglucosidase with concentration of 3500 U/kg starch and temperature of saccharification 55°C producedthe best characteristics of liquid sugars from starch of taro potato.
Keywords: 50